ANTARA KARYA FOTO MODEL DARWIS TRIADI DAN JHONNY HENDARTA - Yulianto, Arif (KEMADHA, 2012)
When mentioning Photography , people will always be attached to the name Derwis Triadi . Andreas Triadi Derwis is an icon of photography in Indonesia . World Photography in Indonesia, we also know some professional photographers who dominate the field of commercial and artistic photography Jhonny Hendarta one of them is living in Jogjakarta . They can both draw on the ideas in his mind and forth in his works . The main characteristic picture of the woman who successfully lies in precisely understanding the character , and given light precisely on the photo . Inspiration is key to shooting photography , inspiration distinguishes a work with the work of others . Proper shadows will make a photograph has a strong character . Both works show the character on each model , the similarity between the chemistry and mood photographer to produce images with the model properly . It is interesting to Jhonny work that he managed to combine the techniques of photography , art elements , and elements of the local Indonesian completely on his work , while the work of gathering light Derwis , artist and model poses on camera shots .